Non-Muslim provinces under early Islam Islamic rule and Iranian legitimacy in Armenia and Caucasian Albania - Vacca, Alison (Cambridge studies in Islamic civilization, 2017)
Eighth- and ninth-century Armenia and Caucasian Albania were largely Christian provinces of the then Islamic Caliphate. Although they formed a part of the Iranian cultural sphere, they are often omitted from studies of both Islamic and Iranian History. In this book, Alison Vacca uses Arabic and Armenian texts to explore these Christian provinces as part of the Caliphate, identifying elements of continuity from Sasanian to caliphal rule, and, more importantly, expounding on significant moments of change in the administration of the Marwanid and early Abbasid periods. Vacca examines historical narrative and the construction of a Sasanian cultural memory during the late ninth and tenth centuries to place the provinces into a broader context of Iranian rule. This book will be of benefit to historians of Islam, Iran and the Caucasus, but will also appeal to those studying themes of Iranian identity and Muslim-Christian relations in the Near East.